Teacher’s Understanding of Ethnoscience-Based Chemistry Learning in Papua - Dewi Natalia Marpaung; Heri Retnawati; Retno Arianingrum (Universitas Lambung Mangkurat, 2025)
This research aims to explore information regarding perceptions of chemistry teachers' understanding of the development of ethnoscience-based chemistry learning in the independent curriculum in Merauke. This research uses a qualitative method with survey and interview methods, especially focusing on the integration of local wisdom in chemistry learning. The participants in this study were 11 chemistry teachers who have implemented ethnoscience-based learning. Data was analyzed by reducing data, displaying data, drawing conclusions/verification. The aspects explored in this research consist of aspects of teachers' understanding of ethnoscience, use of local wisdom in learning, obstacles faced in implementation, availability of resources and materials, relevance to the curriculum, level of student involvement and teacher motivation in implementing ethnoscience. The research results show that the majority of teachers have positive perceptions of ethnoscience learning, especially in relation to student understanding and motivation in teaching. However, obstacles such as teachers' lack of understanding to relate chemistry material to local wisdom, availability of resources and materials are still lacking, not all material can be applied to local cultural wisdom. This indicates that ethnoscience has great potential to be improved to support the quality of chemistry learning. although more support is needed to optimize its implementation, especially training for teachers regarding understanding the application of ethnoscience in chemistry material.